Inhibition of colon cancer K-RasG13D mutation reduces cancer cell proliferation but promotes stemness and inflammation via RAS/ERK pathway - Qi, Yan; Zou, Hong; Zhao, XiaoHui; Kapeleris, Joanna; Monteiro, Michael; Li, Feng; Xu, Zhi Ping; Deng, Yizhen; Wu, Yanheng; Tang, Ying; Gu, Wenyi (Frontiers in Pharmacology, 2022)
K-Ras is a well-studied oncogene, and its mutation is frequently found in epithelial cancers like pancreas, lung, and colorectal cancers. Cancer cells harboring K-Ras mutations are difficult to treat due to the drug resistance and metastasis properties. Cancer stem cells (CSCs) are believed the major cause of chemotherapeutic resistance and responsible for tumor recurrence and metastasis. But how K-Ras mutation affects CSCs and inflammation is not clear. Here, we compared two colon cancer cell lines, HCT-116 and HT-29, with the former being K-RasG13D mutant and the latter being wildtype. We found that HCT-116 cells treated with a K-Ras mutation inhibitor S7333 formed significantly more tumor spheroids than the untreated control, while the wild type of HT-29 cells remained unchanged. However, the size of tumor spheroids was smaller than the untreated controls, indicating their proliferation was suppressed after S7333 treatment. Consistent with this, the expressions of stem genes Lgr5 and CD133 significantly increased and the expression of self-renewal gene TGF-β1 also increased. The flow cytometry analysis indicated that the expression of stem surface marker CD133 increased in the treated HCT-116 cells. To understand the pathway through which the G13D mutation induced the effects, we studied both RAS/ERK and PI3K/Akt pathways using specific inhibitors SCH772984 and BEZ235. The results indicated that RAS/ERK rather than PI3K/Akt pathway was involved. As CSCs play the initial role in cancer development and the inflammation is a vital step during tumor initiation, we analyzed the correlation between increased stemness and inflammation. We found a close correlation of increased Lgr5 and CD133 with proinflammatory factors like IL-17, IL-22, and IL23. Together, our findings suggest that K-RasG13D mutation promotes cancer cell growth but decreases cancer stemness and inflammation thus tumorigenesis and metastasis potential in colon cancer. Inhibition of this mutation reverses the process. Therefore, care needs be taken when employing targeted therapies to K-RasG13D mutations in clinics.